2018
DOI: 10.1093/nar/gky918
|View full text |Cite
|
Sign up to set email alerts
|

Bre1-dependent H2B ubiquitination promotes homologous recombination by stimulating histone eviction at DNA breaks

Abstract: Repair of DNA double-strand breaks (DSBs) requires eviction of the histones around DNA breaks to allow the loading of numerous repair and checkpoint proteins. However, the mechanism and regulation of this process remain poorly understood. Here, we show that histone H2B ubiquitination (uH2B) promotes histone eviction at DSBs independent of resection or ATP-dependent chromatin remodelers. Cells lacking uH2B or its E3 ubiquitin ligase Bre1 exhibit hyper-resection due to the loss of H3K79 methylation that recruits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 65 publications
(91 reference statements)
5
35
0
Order By: Relevance
“…Overall, loss of RNF20-RNF40 gives rise to increased damage and renders cells sensitive to DSB-inducing agents [ 90 ]. These findings mimic those in yeast depleted for Bre1, the homolog to RNF20-RNF40 [ 93 , 94 , 95 ]. Similarly, use of H2BK120/125R, an H2B mutant that cannot be ubiquitinated (K125 can be ubiquitinated in the event that K120 is unavailable) also delayed resolution of DSB foci.…”
Section: Histone Ubiquitination As a Response To Dsbssupporting
confidence: 69%
See 1 more Smart Citation
“…Overall, loss of RNF20-RNF40 gives rise to increased damage and renders cells sensitive to DSB-inducing agents [ 90 ]. These findings mimic those in yeast depleted for Bre1, the homolog to RNF20-RNF40 [ 93 , 94 , 95 ]. Similarly, use of H2BK120/125R, an H2B mutant that cannot be ubiquitinated (K125 can be ubiquitinated in the event that K120 is unavailable) also delayed resolution of DSB foci.…”
Section: Histone Ubiquitination As a Response To Dsbssupporting
confidence: 69%
“…Furthermore, promoting chromatin decondensation by treatment with chloroquine, trichostatin A, or hypotonic buffer restores IRIF formation in RNF20-depleted cells [ 90 ]. It has been proposed in yeast that monoubiquitination of H2B facilitates the accumulation of downstream repair factors at sites of breaks through altering histone dynamics and promoting nucleosome disassembly, reminiscent of its known role in transcriptional elongation [ 94 , 98 , 99 ]. In support of this, H2B ubiquitination has been shown to influence crosstalk with other histone marks including H4K20 methylation and H4K9 methylation that in turn may impact the downstream recruitment of DSB factors [ 94 , 95 ].…”
Section: Histone Ubiquitination As a Response To Dsbsmentioning
confidence: 99%
“…Our results indicate that nucleosome peaks around the TSS are slightly increased in the dbl2Δ mutant compared with the wild-type (Figure 7A ), indicating that Dbl2 could be involved in removing excess nucleosomes. In support of this notion, Rad51 overexpression stimulates the histone eviction at DSBs in bre1Δ mutant ( 123 ). In wild-type cells, Bre1 stimulates histone eviction at DSBs by H2B ubiquitination ( 123 ).…”
Section: Discussionmentioning
confidence: 74%
“…In support of this notion, Rad51 overexpression stimulates the histone eviction at DSBs in bre1Δ mutant ( 123 ). In wild-type cells, Bre1 stimulates histone eviction at DSBs by H2B ubiquitination ( 123 ). Furthermore, a recent study analysing regulators of heterochromatin spreading in different chromatin contexts demonstrated that the HIRA histone chaperone and genes involved in HR pathway, such as rad50 and sfr1 , act in opposite ways ( 124 ).…”
Section: Discussionmentioning
confidence: 74%
“…RNF20 is known to be required to regulate chromosome structure by monoubiquitinating histone H2B at lysine 123 (H2BK123) in budding yeast and at lysine 120 (H2BK120) in humans (12,13). H2BK120ub is a key histone modification that plays critical roles in gene transcriptional regulation and higher order chromatin organization in many species (8,(14)(15)(16)(17)(18)(19)(20). Ubiquitination of histone H2B (H2Bub) has been reported to be associated with highly expressed active genes in human cells (15,21).…”
Section: Introductionmentioning
confidence: 99%